Long-term relationship between investment and economic growth: A cointegration analysis of OECD countries - Fisnik Morina; Valdrin Misiri; Fitore Gashi (European Journal of Government and Economics (EJGE), 2023)
This article investigates the impact of domestic investments on economic growth in OECD countries from 2000 to 2020. It identifies factors affecting economic growth and analyzes the relationship between domestic investments and economic growth using econometric models. Empirical data from the World Bank, IMF, and OECD reports supports the positive impact of domestic investments on economic growth in OECD countries. The study also finds a long-term causality between GDP and Gross Fixed Capital Formation (GFCF). These findings offer valuable insights into investment dynamics and their effects on economic growth, informing governments and policymakers in OECD countries.
Keywords: E2; G11; E42; F3; F43; 330; economic growth; investments; OECD countries